Informational Requirements of A Mobile-Based System to Manage the Treatment of Stimulant Abusers - Marjan Ghazi Saeedi; Masoomeh Amin Esmaeili; Sharareh Rostam Niakan Kalhori; Marzyeh Sadat Askari (Tehran University of Medical Sciences, 2019)
Background and Aim: Stimulants are among the most dangerous substances because of their physical and psychological side effects. The process of treating stimulant abusers is so complicated that makes the treatment very difficult. The aim of the current study is to identify the bits of information needed for the design and development of a mobile application system and a web-based application program to improve the treatment management of stimulant abusers.  Materials and Methods: This study is a cross-sectional study in which the community and the sample are matched. All participators work at Iranian National Center for Addiction Studies(INCAS) as stimulant abuse care givers. The data collection tool was a researcher made questionnaire based on the Likert scale, and its validity approved by experts. In addition, the reliability determined by Cronbach alpha method with the score 0/74 analyzed via SPSS.  Results: Items that got more than 50% of the participants' acceptance were identified as the information needed for the system. The most influential items were education and motivational messages with 100% of experts' agreement. Trauma history and medication therapy, however, got less than 50% and were removed. Other items were put into the study by gaining an average of more than 80% of the experts' agreement.   Conclusion: Emerging technologies in the field of heath can play a significant role in the optimization of stimulant abuse treatment by facilitating the treatment process, increasing the patient participation in the process of treatment, and reducing the costs of patients' lapse and relapse.